2020
DOI: 10.1186/s13765-020-00525-x
|View full text |Cite
|
Sign up to set email alerts
|

Bromelia karatas and Bromelia pinguin: sources of plant proteases used for obtaining antioxidant hydrolysates from chicken and fish by-products

Abstract: In the present study, we evaluated new sources of plant proteases from fruits of Bromelia karatas (BK) and Bromelia pinguin (BP) to obtain antioxidant hydrolyzates/bioactive peptides (BPs) derived from chicken by-products (CH) and fish by-products (FH). The profile of the peptides was identified by reverse-phase high-resolution liquid chromatography (RP-HPLC) and the size weight distribution by molecular exclusion chromatography (SEC). The hydrolysates obtained with BK in both sources of by-products showed gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
0
9
0
1
Order By: Relevance
“…Promising results have been published using emerging plant proteases as reported by Romero‐Garay et al [207] . The authors evaluated the application of plant proteases derived from Bromelia karatas (BK) and Bromelia pinguin (BP) for antioxidant hydrolysates/bioactive peptides production through fish waste hydrolysis.…”
Section: Plant Protease Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Promising results have been published using emerging plant proteases as reported by Romero‐Garay et al [207] . The authors evaluated the application of plant proteases derived from Bromelia karatas (BK) and Bromelia pinguin (BP) for antioxidant hydrolysates/bioactive peptides production through fish waste hydrolysis.…”
Section: Plant Protease Applicationsmentioning
confidence: 99%
“…In concordance with these, the synergic effect between plant proteases with animal enzymes for fish waste hydrolysis is reported in the literature. [204] Promising results have been published using emerging plant proteases as reported by Romero-Garay et al [207] The authors evaluated the application of plant proteases derived from Bromelia karatas (BK) and Bromelia pinguin (BP) for antioxidant hydrolysates/bioactive peptides production through fish waste hydrolysis. The plant proteases were extracted and semi-purified using simple procedures.…”
Section: Fish Protein Hydrolysismentioning
confidence: 99%
“…However, bitterness of protein hydrolysate is an important undesirable aspect for various applications, hence, for the removal of bitterness from protein hydrolysates, exopeptidase treatment, Maillard reaction, plastein reaction and encapsulation are being worked on ( Fu et al, 2019 ) , this would potentiate the acceptance of peptides by consumers. Hydrolysis, and in particular enzymatic hydrolysis allows obtaining hydrolysates with a high degree of hydrolysis which in turn results in a high yield (Gajanan et al, 2016) with a higher release of small peptides favoring their functional properties such as their solubility, emulsification and foam formation ( Zou et al, 2021 ), at this point it should be noted that poultry by-products have presented yield values between 46% and 65% with production of peptides with biological activity ( Romero-Garay et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The fruits Bromelia pinguin and B. karatas are considered to be a source of plant proteases with promising properties for industrial and therapeutic applications, and to obtain bioactive peptides (Mazorra-Manzano et al, 2018). Recent studies have shown that hydrolysed bioactive peptides can be obtained from proteases extracted from B. pinguin and B. karatas, and from other sources of proteins (Meza-Espinoza et al, 2018;Romero-Garay et al, 2020). The objective of the present work was to evaluate the health effects of peptides obtained from CH by the action of plant proteases of B. pinguin (BP), B. karatas (BK), and bromelain (BRO), in a model of induced MS, on the different biochemical markers and hepatocellular lesions that were altered by the development and prevalence of MS.…”
Section: Introductionmentioning
confidence: 99%